(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Acute coronary syndrome (ACS) is a major cause of morbidity and mortality worldwide. Emerging evidence suggests that vitamin D deficiency, elevated serum homocysteine levels, and lipid abnormalities contribute significantly to the development and progression of coronary artery disease. This study was conducted to evaluate the association of serum vitamin D, serum homocysteine, and lipid profile in patients with ACS. Methodology: This hospital-based observational study was conducted in the Department of Emergency Medicine at from February 2025 to December 2026. A total of 96 patients diagnosed with ACS, including ST-segment elevation myocardial infarction (STEMI), non-ST-segment elevation myocardial infarction (NSTEMI), and unstable angina, were included in the study. Serum vitamin D, serum homocysteine, and lipid profile parameters were estimated using the Vitros 5600 automated analyzer. Statistical analysis was performed using SPSS version 25.0, and a p-value <0.05 was considered statistically significant. Results: Among the 96 ACS patients, 35.41% had STEMI, 33.33% had NSTEMI, and 31.25% had unstable angina. Vitamin D deficiency (<20 ng/dl) was observed in 46.87% of patients, while 32.29% had insufficiency and only 20.83% had sufficient levels. Elevated homocysteine levels were noted in the majority of patients, with 59.38% showing intermediate elevation and 13.54% having severely elevated levels. Low HDL cholesterol levels (<40 mg/dl) were present in 75% of patients. Diabetes mellitus and hypertension were identified in 75% and 58.33% of patients respectively. Smoking was reported in 40.63% of patients. Conclusion: Vitamin D deficiency, elevated serum homocysteine levels, and low HDL cholesterol were commonly observed among ACS patients and may play a significant role in the pathogenesis of acute coronary syndrome. Early identification and management of these modifiable biochemical risk factors may help improve cardiovascular outcomes and reduce disease burden.